TANGGUNG JAWAB AKUNTAN PUBLIK ATAS LAPORAN KEUANGAN YANG OVERSTATED DI PASAR MODAL - Windy Sri Wahyuni; Bismar Nasution; Mahmul Siregar; Suhaidi Suhaidi (USU LAW JOURNAL, 2014)
ABSTRACTPublic Accountant is supporting of professional the capital market that help company in implementing the principle of transparency. Public accountant have authority to review the financial statements that independent to produce a fairness opinion regarding the financial statements. Liability of public accountant on the financial statements only to the opinion that it provides. The problems discussed in this study is the independence of public accountant in the capital market, public accountant opinion on the financial statements in the capital market, and liability of public accountant on the financial statements that overstated in the capital market. This study were analyzed by using the theory of professional liability and the principles of transparency in the capital market. Based on these results, the independence of public accounting in capital market include aspects of the appearance of independence and independence of thought, public accountant opinion on the financial statements in capital market determined if the financial statements present fairly in all material respects that produces unqualified opinion, the liability of public accountant on the financial statements that overstated in the capital markets of the opinion that it provides, including losses incurred and public accountant may be given administrative sanctions, civil penalties and criminal sanctions.Keywords: Public Accountant Liability, Financial Statements overstated.